Digital Human Resource Capabilities and Strategic Success in Iraqi Tourism: Kapasitas Sumber Daya Manusia Digital dan Kesuksesan Strategis dalam Pariwisata Irak - Firas Naji Hatem; Azhar Ali Ahmed (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Digital transformation has become a defining feature of contemporary organizational management, particularly in service-oriented sectors such as tourism. Specific Background Tourism companies in Iraq face increasing pressure to modernize human resource practices through digital knowledge, technical skills, and digital leadership. Knowledge Gap Despite this necessity, limited empirical evidence explains how digital human resource capabilities are systematically linked to strategic success in Iraqi tourism organizations. Aims This study aims to examine the relationship between digital human resource capabilities and strategic success dimensions within tourism companies operating in Baghdad, Karbala, and Najaf. Results Using a descriptive-analytical approach and data from 123 managers and employees, the findings reveal a statistically significant relationship between digital capabilities and strategic success, with digital leadership showing the strongest explanatory contribution. Novelty The study offers context-specific empirical evidence from religious tourism organizations, integrating digital human resource capabilities with strategic success indicators. Implications The findings provide practical insights for tourism managers and policymakers seeking to strengthen adaptation, survival, and growth through structured digital human capital development. Keywords: Digital Human Resource Capabilities, Strategic Success, Tourism Companies, Digital Leadership, Iraq Key Findings Highlights: Digital leadership demonstrates the highest contribution to organizational adaptability and continuity. Technical skills remain the most operationally developed capability among tourism firms. Strategic outcomes are strongly explained by combined digital capability dimensions.